The effect of career counseling based on Krumboltz planned happenstance approach on enhancement of perceptible entrepreneurship capabilities students - L. Dindoost; M. R. Abedi; F. Bahrami (پژوهش‌های علوم شناختی و رفتاری, 2013)
The purpose of this study was to examine the effectiveness of career counseling based on Krumboltz planned happenstance approach on enhancement of entrepreneurship capabilities of the Isfahan university students. The population of the study consisted of students of the university of Isfahan, from which a sample of 50 students were selected. The Entrepreneurship Capabilities Scales were administered to all subjects at the pre, post and follow-up stages. The experimental group received Krumboltz planned happenstance approach training, while the control group was in the waiting list. In order to investigate the effectiveness of lasting, a follow-up test was held after twenty days from the last intervention session. The results of analysis of covariance showed that the two groups were significantly different in entrepreneurship capabilities both in the post- (P=0.002) and follow-up tests (P=0.009).